Analysis of Factors That Influence the Income of Gambir Farmers in Nagari Simpang Kapuak, Mungka District - Rahmadani, Novita; Anwar, Syaiful; Pratiwi, Resi; Weriantoni, Weriantoni (Jurnal Ekonomi Balance, 2023)
Gambir is a kind of dried sap leaf extracted from the crushed leaves and young twigs of the gambier plant. In Indonesia it is generally used for betel nut and medicine. This study aims to determine the effect of capital, labor and price variables on the income of gambir farmers in Nagari Simpang Kapuak, Mungka District. The type of research used is by using the field research method (field research), namely research carried out by going down to the field / research location. Data collection was carried out by means of interviews, questionnaires and direct observation. The sample used was 50 gambier farmers using a sample collection technique by direct field survey or census. The analytical method used multiple linear regression. The results showed that the capital variable had a positive and significant effect on the income of gambir farmers in Nagari Simpang Kapuak with a t-count sig. 0.000 <0.005. price variable with a sig t-count value, 0.522 > 0.005. This means that the labor and price variables have no positive and significant effect on the income of gambier farmers in Nagari Simpang Kapuak, Mungka District, Fifty City District.